2016
DOI: 10.1016/j.precisioneng.2015.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the energy repartition in micro electrical discharge machining

Abstract: International audienceThis paper presents a new approach for the recording of the total quantity of energy exchanged during the micro electrical discharge machining (EDM) process. In particular, this approach allows for the estimation of the percentage of energy absorbed by the two electrodes (tool and workpiece) using a combination of theoretical models and experimental results, thanks to an advanced discharges measuring approach. An experimental campaign was executed on a Sarix SX200 micro-EDM machine with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Of the total energy supplied through the electrical circuit, most is lost to the dielectric; and experimentations on SS 304 using tungsten wire tool electrode coupled with electro-thermal modelling and simulation show that only 6.78% of the total pulse energy is transmitted to the cathode and 7.37% to the anode [63]. While in another experimentation, on aluminium workpiece using WC tool electrode, energy repartition to cathode is estimated to be around 1%-2% and to anode is estimated around 11%-18% [64]. Although the fundamentals of µ-EDM are same as macro EDM, the power density available at the workpiece in µ-EDM is about 30 times larger [65] as a consequence of shorter discharge durations.…”
Section: Introductionmentioning
confidence: 99%
“…Of the total energy supplied through the electrical circuit, most is lost to the dielectric; and experimentations on SS 304 using tungsten wire tool electrode coupled with electro-thermal modelling and simulation show that only 6.78% of the total pulse energy is transmitted to the cathode and 7.37% to the anode [63]. While in another experimentation, on aluminium workpiece using WC tool electrode, energy repartition to cathode is estimated to be around 1%-2% and to anode is estimated around 11%-18% [64]. Although the fundamentals of µ-EDM are same as macro EDM, the power density available at the workpiece in µ-EDM is about 30 times larger [65] as a consequence of shorter discharge durations.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Rigacci et al [1] shown that in the life of the machine tool operating costs account for more than 20% of PC. Bigot et al [2] concluded that in the US, the electricity used for machine tools is up to 80% produced from fossil fuels, this process will generate a significant amount of CO 2 . Aggarwal et al [3] showed that the PC in the machining process is greatly influenced by the cutting mode parameters.…”
Section: Introductionmentioning
confidence: 99%